Análisis comparativo del efecto de ácido orgánicos en dietas para crecimiento y engorde de pollos de carne. - Iza Saltos, Fabiola Del Rocio (2015)
The present work "COMPARATIVE ANALYSIS ON THE EFFECT OF ORGANIC ACID LEVELS IN DIETS FOR GROWTH AND BROILER CHICKEN MEAT", aims to compare the results of two studies conducted previously using organic acids (Formycine Gold: liquid and solid). A design was completely randomized (CRD) with four levels of an organic acid and five replicates for each test. The results were processed using the Tukey significance test with a probability of 5%. The variables measured in each of the research were: Food Consumption (CA), weight gain (GP), feed conversion (CA), the channel performance and mortality. The tested treatments were: T1: control treatment, 100 g Formycine t2, t3 Formycine 200 g. , 300 g Formycine t4. According to Tukey (P <0.05), related to variable food consumption in trial one T3 treatment was 5393g. , Proving to be the best. In trial two best treatment was the T3 with 5057.4g. In the variable gain weight the best treatments were: in the trial one, best treatment resulted T2 2236.1gy in trial two, treatment T4 with 2960 g. In the variable feed conversion, the best treatments were: T2 and T3 treatments with 2.43% in the trial one and the T4 treatment with 1.70% in trial two. As for the performance variable channel, the best results were T3 treatment with 81.48% in trial one; in trial two proved to be the best treatment T4 with 84.08%. We conclude that using organic acid to a level of 300 g per 100 kg of pet food diets for broilers in all its physiological phases, an improvement was obtained in the productive performance of the same (weight gain and feed conversion) . It also concludes that to improve results in the carcass (live weight, carcass weight and carcass yield) can be used organic acids in all physiological stages.